Surfactant Remediation of LNAPL Contaminated Soil; Effects of adding alkaline and foam producing substances (Iranian Journal of Chemical Engineering)
Uncontrolled release of light non aqueous phase liquids (LNAPL) such as diesel, gasoline, fuel oils and lubricating oils from transporting vehicles, pipeline and underground storage tanks (UST) could lead to the migration of contaminants to the subsurface soil and ground water. There is a high interfacial tension (IFT) between LNAPL molecules and water molecules that makes water a non-efficient cleaning material for removing LNAPL from the soil. Nowadays, surfactants (surface active agents) can promote the enhanced removal of LNAPL from the subsurface through mobilization and solubilization. Encouraging results were achieved from laboratory and field results. The aim of this study is to improve the clean up efficiency of surfactant-flooding for two different surfactants; Triton X-100 and Sodium Dodecyl Sulfate which are known as mobilizing and solubilizing surfactants, respectively, by adding alkaline (increasing pH) and foam producing substances. It is shown here that adding alkaline improves the performance of Triton X-100 in removing LNAPL from the contaminated soil by about 8 percent, but spoils the remediating capability of Sodium Dodecyl Sulfate by about 3 percent. Also, adding a foaming agent helps the surfactant solution in removing the LNAPLs out of the soil by more than 5 percent.